Financing of National Parks in Serbia: Case study of PE "NP Tara" - Keča Ljiljana; Marčeta Milica (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
Financial statements are written records that convey the financial activities of a company. The main purpose of this study is to determine, forecast and evaluate the best of economic conditions and company’s performance in the future. For-profit primary financial statements include the balance sheet, income statement, statement of cash flow, and statement of changes in equity. The subject of the research are the categories of income and expenditure, which move in financing PE “NP Tara”. The main goal of this research is to determine the income structure and expenditures in the financing and the trends of their movement in the territory of PE “NP Tara” and establish cause-and-effect relationships among observed quantities. The purpose of the research is comparing the different structures of income and expenses that participate in the financing, during the period of 2008-2021.